Daya Antibakteri Ekstrak Kulit Apel Varietas Manalagi (Malus sylvestris mil.) terhadap Pertumbuhan Lactobacillus acidophilus - Erryska Wira Triandiani; Sulistiyani sulistiyani; Dyah Setyorini (Pustaka Kesehatan, 2020)
Dental problems such as caries are found in the majority of the population of Indonesia. Dental caries is caused by several factors, host, bacteria, substrate and time. The bacteria in deeper caries is Lactobacillus acidophilus. To overcome this problem using synthetic mouthwash containing chlorhexidine, but have it mutagenic effects in the oral cavity. Another alternative is to use natural ingredients that have antibacterial power and smaller side effects. Apple peels which not used by the people is thrown away. Apple peels contains more polyphenols which have antibacterial effect. The aim of this study is knowing the antibacterial activity of manalagi apple peel extract in inhibiting L. acidophilus’s growth. This study used an experimental post-test only control group design with a well diffusion method using 6 groups of samples per treatment in 4 repetitions. The sample consisted of 4 treatment groups namely manalagi apple peel extract concentration of 100%, 50%, 25%, 12.5%, positive control group (clorhexidine 0.2%), and negative control group (sterile aquades). The results of the study showed that of all treatment groups of apple peel extract in all concentrations can inhibit growth of L. Acidophilus.